DINAMIKA SOSIALISASI PENDEKATAN KURIKULUM MERDEKA DI SMPN 5 TALANG KELAPA KABUPATEN BANYUASIN - Aisyah Anis; Dinda Amalia; Abdurrahmansyah; Inka Wahyu Khairunnisa; Yolanda Apriliatsani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The implementation of the Merdeka Curriculum is a significant initiative by the Indonesian government aimed at transforming the education system to be more adaptive, contextual, and student-centered. The success of this policy largely depends on how effectively it is communicated to teachers at the school level. This study aims to explore how the Merdeka Curriculum was introduced at SMPN 5 Talang Kelapa in Banyuasin Regency and to identify factors influencing teachers’ understanding and its implementation in practice. This research employed a qualitative method with a case study design. Data were collected through in-depth interviews with the principal, vice principal for curriculum, and teachers involved in the implementation. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that the dissemination of the Merdeka Curriculum was carried out through internal meetings, teacher training sessions, and participation in workshops organized by external institutions. Effective communication played a crucial role in enhancing teachers’ understanding and encouraging a shift toward more engaging and student-centered teaching practices. However, several challenges remain, including limited facilities and resources, variations in teachers’ competencies, and technical issues related to digital learning management. This study provides insights into curriculum policy communication at the school level and offers strategic recommendations to improve ongoing implementation.